THE ANALYSIS OF PERCEPTION OF WOMEN IN NIQAB AGAINST POLYGAMY PRACTICE IN INDONESIA - Fitriah M. Suud; Moh Toriqul Chaer; Masyhuri Masyhuri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The phenomenon of veiled women in Indonesia has significant development. The use of the niqab is a symbol of the rise of Islam in the post-modern era. A niqab is also an anti-thesis of modern lifestyles that tend to be hedonistic and completely open. This research focuses explicitly on ethnographers working models using the phenomenology paradigm. This research explores women who cover their faces, and why they are more accepting of polygamy. The author found reasons for men to do polygamy and why women in Indonesia reject polygamy practices. The results found that women wear the niqab because, first, as orders from their husbands, second because of inner awareness caused by their understanding of religious education. The practice of women in niqab becomes a kind of artifact of the loyalty of a woman and is directly proportional to the issue of polygamy. The modes used as the legitimacy of men for polygamy, among others, are secret marriage, falsification of self-identity, second marriage without the first wife's consent, coercion of the granting of permission, and consent of the first wife by the husband with various forms of violence and intimidating force